Minimum void length scale control in level set topology optimization subject to machining radii. (December 2016) - Liu, Jikai; Yu, Huangchao; Ma, Yongsheng
Abstract: This paper presents a minimum void length scale control method for structural topology optimization. Void length scale control has been actively investigated for decades, which intends to ensure the topology design manufacturable given the machining tool access. However, only a single lower bound has been applied in existing methods, which does not fit the multi-stage rough-to-finish machining. To fix this issue, the proposed minimum void length scale control method employs double lower bounds which corresponds to the rough and finish machining operations, respectively. This method has been implemented under the level set framework. For technical details, the rough machining lower bound is satisfied by developing a signed distance-related constraint, which ensures enough space for the rough machining tool movement and thus, guarantees the machining efficiency. The finish machining lower bound is addressed through the curvature flow control, which ensures the small features manufacturable and also a good finish dimension and surface. Through a few numerical case studies, it is proven that the minimum void length scale can be effectively controlled without sacrificing much of the structural performance. Highlights: This paper presents a minimum length scale control method for structural topology optimization. Two lower bounds are concurrently applied which corresponds to the rough and finish machining operations, respectively. The rough machining lower bound is satisfied by developing a signed distance-related constraint. The finish machining lower bound is addressed through the curvature flow control.